Comparison of kick exercises using feet full inside and back of the foot for shooting accuracy - Sufyansyah, Taufiq; Widyastuti, Suci Rahayu; Suganda, Mikkey Anggara (Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine the effect of shooting practice with the inner instep and full instep on the shooting accuracy of students of the Porseka Football School (SSB), Kaliwulu Village, Plered District, Cirebon Regency. Football students in this study were limited to 13-14 years old. This study uses an experimental method with a "two group pre test post test design" design. The population in this study is 124 students of the Porseka Football School (SSB), Kaliwulu Village, Plered District, Cirebon Regency. Samples taken from purposive sampling results, with criteria namely; (1) students of the Porseka Football School (SSB) Kaliwulu Village, Plered District, (3) aged 13-15 years, (3) have participated in training for at least 6 months. Based on these criteria, 24 people are met. The instrument used for the shooting accuracy test is the accuracy of the kick to the goal with data analysis using the t-test. The results of the analysis showed that: (1) There was an effect of shooting drills on the shooting accuracy of students of the Porseka Football School (SSB), Kaliwulu Village, Plered District, Cirebon Regency, with a t count of 7,178 > t table 2.20, and a significance value of 0.000 < 0.05, with a percentage increase of 39.29%. (2) There was an effect of full reed shooting practice on the shooting accuracy of students of the Porseka Football School (SSB) Kaliwulu Village, Plered District, Cirebon Regency, with a tally of 3,240 > t table 2.20, and a significance value of 0.008 < 0.05, with a percentage increase of 17.73%. (3) Shooting practice with the inner instep is better than shooting practice with the full instep on the shooting accuracy of students of the Porseka Football School (SSB) Kaliwulu Village, Plered District, Cirebon Regency, with t calculation 3.669 > t table = 2.07 and sig. 0.001 < 0.05, and the difference in posttest scores was 5.25. The conclusion that can be drawn from this study is that there is an effect of variation training on the shooting accuracy of students of the Porseka Football School (SSB), Kaliwulu Village, Plered District, Cirebon Regency.